MODEL PENINGKATAN KUALIFIKASI SARJANA S-1 BAGI GURU MADRASAH DAN GURU PAI PADA SEKOLAH MELALUI DUAL MODE SYSTEM - Nur Munajat Nur Munajat (Jurnal Pendidikan Agama Islam, 2014)
This study aimed to describe the process of implementation, knowing the results of learning, find problems, and find solutions for the improvement of educational qualification improvement program S1 for Madrasa teachers and PAI (Islamic Education) teachers through dual mode system in Tarbiya and Teaching Faculty of UIN Sunan Kalijaga Yogyakarta.This research is a qualitative descriptive study, the subject of research, program managers, lecturers, and students participating in the Dual Mode System Program. Data collected through observation, interviews, and documentation. Data analysis using inductively mindset.Results show that: 1). The process of implementation of the program for the improvement of educational qualifications S1 Madrasah teachers and PAI teachers through a dual mode system in Tarbiya and Teaching Faculty of UIN Sunan Kalijaga Yogyakarta, has been performing well, with reference to the established regulations; 2). Learning outcomes 80% categorized as very satisfactory, and 20%, satisfactory; 3). Problem Management covers eight aspects, namely the curriculum, learning, student recruitment, system conversion, distribution module, LPTKs relationships with partners, completion of thesis, and quality assurance. 4). The suggested solution is the improvement of curriculum and learning, new student recruitment system, conversion, distribution module, the system of cooperation with LPTKs Partners, and improvement of quality assurance commitment.